The star formation properties of the observed and simulated AGN Universe: BAT versus EAGLE - Jackson, Thomas M.; Rosario, D J; Alexander, D M; Scholtz, J; McAlpine, Stuart; Bower, R G (Monthly notices of the Royal Astronomical Society, 2020)
In this paper, we present data from 72 low-redshift, hard X-ray selected active galactic nucleus (AGN) taken from the Swift-BAT 58 month catalogue. We utilize spectral energy distribution fitting to the optical to infrared photometry in order to estimate host galaxy properties. We compare this observational sample to a volume- and flux-matched sample of AGN from the Evolution and Assembly of GaLaxies and their Environments (EAGLE) hydrodynamical simulations in order to verify how accurately the simulations can reproduce observed AGN host galaxy properties. After correcting for the known +0.2 dex offset in the SFRs between EAGLE and previous observations, we find agreement in the star formation rate (SFR) and X-ray luminosity distributions; however, we find that the stellar masses in EAGLE are 0.2-0.4 dex greater than the observational sample, which consequently leads to lower specific star formation rates (sSFRs). We compare these results to our previous study at high redshift, finding agreement in both the observations and simulations, whereby the widths of sSFR distributions are similar (∼0.4-0.6 dex) and the median of the SFR distributions lie below the star-forming main sequence by ∼0.3-0.5 dex across all samples. We also use EAGLE to select a sample of AGN host galaxies at high and low redshift and follow their characteristic evolution from z = 8 to z = 0. We find similar behaviour between these two samples, whereby star formation is quenched when the black hole goes through its phase of most rapid growth. Utilizing EAGLE we find that 23 per cent of AGN selected at z ∼ 0 are also AGN at high redshift, and that their host galaxies are among the most massive objects in the simulation. Overall, we find EAGLE reproduces the observations well, with some minor inconsistencies (∼0.2 dex in stellar masses and ∼0.4 dex in sSFRs).